2014
DOI: 10.1590/1676-06032014012914
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of small land mammals in a subtropical Atlantic forest in the western region of the state of Santa Catarina, southern Brazil

Abstract: MAESTRI, R., GALIANO, D., KUBIAK, B.B., MARINHO, J.R. Diversity of small land mammals in a subtropical Atlantic forest in the western region of the state of Santa Catarina, southern Brazil. Biota http://dx.doi.org/10.1590/1676-06032014012914Abstract: Small land mammals possess features that significantly influence the dynamics of ecosystems and participate in various levels of the food web. In the Brazilian Atlantic Forest the richness of these animals is high, which makes them even more ecologically and numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Our fragments are in the southern portion of the Atlantic Forest biome, outside the tropical region. Studies with a similar methodology in the Atlantic Forest have found between six to 21 species, and, in general, studies in lower latitudes had greater species richness (e.g., Pardini et al, 2005;Vieira et al, 2009;Lima et al, 2010;Maestri et al, 2014). The PET itself, the most preserved forest area in the southernmost portion of Atlantic Forest, had lower species richness than other well-preserved forests further north (Melo et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…Our fragments are in the southern portion of the Atlantic Forest biome, outside the tropical region. Studies with a similar methodology in the Atlantic Forest have found between six to 21 species, and, in general, studies in lower latitudes had greater species richness (e.g., Pardini et al, 2005;Vieira et al, 2009;Lima et al, 2010;Maestri et al, 2014). The PET itself, the most preserved forest area in the southernmost portion of Atlantic Forest, had lower species richness than other well-preserved forests further north (Melo et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…Trata-se de um pequeno roedor endêmico da mata atlântica, de hábito semifossorial e dieta insetívoro-onívora (PAGLIA et al, 2012). Isso contrasta com os outros estudos sobre pequenos mamíferos na mata atlântica do sul do Brasil, nos quais Akodon montensis é o táxon mais frequente (LIMA et al, 2010;MELO et al, 2011;BALIEIRO et al, 2015) ou o segundo mais frequente (GRAIPEL et al, 2006;MAESTRI et al, 2014). Em termos de comparação, Cherem & Althoff (2019) registraram 43 capturas (81,1%) de Akodon sp.…”
Section: Discussionunclassified
“…Nessa área, obteve-se uma menor quantidade de amostras fecais de felinos e não foi empregada a captura com armadilhas, o que se refletiu na baixa riqueza do grupo. Entretanto Akodon e Oligoryzomys têm sido reportados como os gêneros predominantes em assembleias de pequenos mamíferos em outras áreas no sul do Brasil (DALMAGRO & VIEIRA, 2005;PETERS et al, 2010;MELO et al, 2011;MAESTRI et al, 2014).…”
Section: Discussionunclassified
“…Historically, the study area has been affected by selective removal of wood and use of the land for cellulose monoculture. Part of the area is now in regeneration process, but is still subject to disturbances, especially illegal hunting (Maestri et al 2014).…”
mentioning
confidence: 99%